The Effect of Interactive Multimedia-Based Learning on Students Mathematical Critical Thinking Ability in the Course of Structure Algebra - Lilis Marina Angraini; Nurmaliza Nurmaliza (Didaktik Matematika, 2022)
The critical thinking ability is fundamental in learning mathematics so it must be possessed by students as prospective teachers. In fact, the students' mathematical critical thinking ability is still relatively low. In this case, one of the causes is the change in learning system from face-to-face to online learning. One effort that can be done to overcome this issue is to apply interactive multimedia-based learning. Current research was further conducted in this matter, aiming to improve students' mathematical critical thinking ability through interactive multimedia-based learning to support online learning. This quantitative research (quasi-experimental) was carried out by involving prospective mathematics teacher students enrolling in the algebraic structure course in 2021/2022 at Universitas Islam Riau (UIR) as the experimental class and prospective mathematics teacher students at Universitas Pasir Pengaraian (UPP) as the control class. The data were further collected through a mathematical critical thinking ability test which were further analyzed through statistical tests. Based on the results of the t-test, there was an increase in students' mathematical critical thinking ability who received a learning process using interactive multimedia.